2018
DOI: 10.1111/jfs.12513
|View full text |Cite
|
Sign up to set email alerts
|

Food safety knowledge, attitude, and food handling practices of household women in Lahore

Abstract: In this study a sample of 1,000 household women from 10 towns of Lahore was collected. Significant difference was observed between education with knowledge, attitude, and practice scores. Data obtained served as baseline knowledge and information for emphasis on continuous improvement on the knowledge of household women. Baseline knowledge and perceptions of household women is crucial to understanding the status of food safety among them, so educational programming, awareness campaigns, trainings, workshops ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
9
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
7
9
3
Order By: Relevance
“…In this study, a good attitude towards food safety was also a significant predictor of good food safety practices. This finding is in line with results from cross-sectional studies conducted in Bole Sub-city, Addis Ababa, 18 Northwest Ethiopia, 20 Debarq Town 29 and Debre Markos Town, Ethiopia, 31 Imo State, Nigeria, 27 Kuwait, 40 Lahore, Pakistan, 28 and Sarawak and Petaling Jaya, Malaysia. 38 , 39 A possible reason for this association is that training in food safety measure packages leads to a good attitude, which may improve the behavior around and practice of food safety.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, a good attitude towards food safety was also a significant predictor of good food safety practices. This finding is in line with results from cross-sectional studies conducted in Bole Sub-city, Addis Ababa, 18 Northwest Ethiopia, 20 Debarq Town 29 and Debre Markos Town, Ethiopia, 31 Imo State, Nigeria, 27 Kuwait, 40 Lahore, Pakistan, 28 and Sarawak and Petaling Jaya, Malaysia. 38 , 39 A possible reason for this association is that training in food safety measure packages leads to a good attitude, which may improve the behavior around and practice of food safety.…”
Section: Discussionsupporting
confidence: 90%
“…The overall prevalence of good food safety practices among model and non-model households was 44.7% (95% CI: 40.5–48.4%) and this prevalence was higher than in studies carried out in Northwest Ethiopia (40.1%), 20 Bole Sub-city in Addis Ababa (27.4%), 18 Arba Minch Town (32.6%), 22 and West Arsi Zone (27.5%), Ethiopia, 26 Imo State, Nigeria (37%), 27 and Lahore, Pakistan (0.3%). 28 This difference may be due to the improvements in health extension service approaches and other community health education services as interventions during the time gap between the studies. For instance, successive training on food hygiene and safety in the current study area could increase good food safety practices, since training is the best intervention through which to improve knowledge, which is a key factor in improving practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 29.1% and 29.4% of the participants, respectively, correctly answered the questions regarding refrigeration and freezing temperatures, which is in line with other studies [ 38 , 39 ]. Since two-thirds of the respondents in our study were women, our results suggest that Saudi women still manage food shopping and food preparation more so than men.…”
Section: Discussionsupporting
confidence: 90%
“…It could be due to that higher education might help to shape or change in behavior of mothers in good attitude toward food safety. Other studies 26,29,37 also revealed that educated mothers had more positive attitudes in relation to food safety and those with respondents that have low educational level had less good attitude level compared to the respondents that have high education level.…”
Section: Discussionmentioning
confidence: 91%